HUBUNGAN PERSEPSI IBU BALITA TERHADAP KUALITAS PELAYANAN DENGAN MINAT KUNJUNGAN KE POSYANDU SEULANGA DI DESA KAMPUNG BELAKANG KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Anggellya Anggellya; Yushida Yushida; Lilis Suryani; Irnawati Irnawati; Fithriany Fithriany (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aim to determine the relationship between the quality of integrated health service posts and the interest of mothers of toddlers in visiting the Seulanga Integrated Health Post, Kampung Belakang Village, Johan Pahlawan District, West Aceh Regency. The type of research used is quantitative research with a descriptive approach.cross sectional. The population in this study were all mothers of babies and mothers of toddlers in Kampung Belakang Village, Johan Pahlawan District, West Aceh Regency, totaling 138 people and the number of samples used was 58 respondents with the techniqueprobability sampling. Data analysis usingUji Chi Square. Mothers who chose poor quality were 21 respondents (36.2%), while those who chose moderate quality were 11 respondents (19.0%) and those who chose high service quality were 26 respondents (44.8%). Mothers who chose low interest were 21 respondents (36.2%), while those who chose moderate interest were 11 respondents (20.7%) and those who chose high interest were 26 respondents (43.1). The results of the statistical test showed a p-value of 0.000 (p < 0.05), which means that there is a significant relationship between the quality of integrated health post services and the interest of mothers of toddlers in visiting. There is a need to improve the overall quality of service, especially in terms of physical facilities such as waiting rooms and the completeness of toddler examination equipment.